1992
DOI: 10.1093/brain/115.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Discrimination Is Abnormal in Parkinson's Disease

Abstract: Temporal discrimination thresholds (TDT) for recognition of paired sensory (tactile, auditory and visual) stimuli given over a wide range of time intervals were assessed in 44 patients with Parkinson's disease (PD) and 20 age-matched normal subjects. A significant increment in TDT for all three sensory modalities was found in PD patients compared with controls. This abnormality was greatly attenuated for about 2 h by a single levodopa/carbidopa (250/25 mg) tablet. A significant correlation was found between di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
294
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(323 citation statements)
references
References 25 publications
23
294
5
Order By: Relevance
“…This finding is supported by work in Parkinsonian (Artieda et al, 1992;Harrington et al, 1998a;Malapani et al, 1998;Elsinger et al, 2003), and Huntington's disease patients (Paulsen et al, 2004). The well established influence of dopamine upon subjective time measurement has led to the suggestion that the basal ganglia, a cluster of nuclei which are heavily innervated by dopamine, may house a time-dependent process, or at least be involved in timing.…”
Section: Time-dependent Processmentioning
confidence: 62%
See 2 more Smart Citations
“…This finding is supported by work in Parkinsonian (Artieda et al, 1992;Harrington et al, 1998a;Malapani et al, 1998;Elsinger et al, 2003), and Huntington's disease patients (Paulsen et al, 2004). The well established influence of dopamine upon subjective time measurement has led to the suggestion that the basal ganglia, a cluster of nuclei which are heavily innervated by dopamine, may house a time-dependent process, or at least be involved in timing.…”
Section: Time-dependent Processmentioning
confidence: 62%
“…Single unit recording studies have shown that some cells in the dorsolateral prefrontal cortex behave in a manner consistent with the integrator concept, systematically increasing or decreasing firing rates along a temporally predictable function during measured delay intervals (Niki and Watanabe, 1979;Matell et al, 2003). As discussed above, the suggestion that modulations of this type in dorsolateral prefrontal cortex are used as the time-varying process is in accord with the observed effects of dopamine upon time measurement (Artieda et al, 1992;Harrington et al, 1998a;Meck, 1996;O'Boyle et al, 1996) since dorsolateral prefrontal cortex receives modulatory dopaminergic inputs (Porrino and Goldman-Rakic, 1982). The observation of increased activity in that region during the measurement of a longer interval is also compatible with this scheme and could be interpreted as evidence for recruitment of additional integration or decay functions.…”
Section: Memory Traces As the Time-varying Processmentioning
confidence: 67%
See 1 more Smart Citation
“…Thus, amygdala neurons have access to an internal clock that processes the time of future reward occurrence. The temporal influence on amygdala neurons might derive from dopamine projections [58] involved in interval timing [59,60].…”
Section: Amygdalamentioning
confidence: 99%
“…After initial negative results (Ivry and Keele 1989), several studies have shown and confirmed an impairment on different timing tasks in PD (e.g. Artieda et al 1992;Pastor et al 1992;Harrington et al 1998a), which is especially prominent when patients are taken off dopaminergic medication (Malapani et al 1998). This deficit is not restricted to motor timing, but is also evident in perception, for example in discrimination of temporal intervals (Hellström et al 1997;Rammsayer and Classen 1997).…”
Section: Introductionmentioning
confidence: 99%